Congenital Zika Syndrome Is Associated With Interferon Alfa Receptor 1 - Azamor, Tamiris; Cunha, Daniela Prado; da Silva, Andréa Marques Vieira; Bezerra, Ohanna Cavalcanti de Lima; Ribeiro-Alves, Marcelo; Calvo, Thyago Leal; Kehdy, Fernanda de Souza Gomes; Manta, Fernanda Saloum de Neves; Pinto, Thiago Gomes de Toledo; Ferreira, Laís Pereira; Portari, Elyzabeth Avvad; Guida, Letícia da Cunha; et al. (Frontiers in Immunology, 2021)
Host factors that influence Congenital Zika Syndrome (CZS) outcome remain elusive. Interferons have been reported as the main antiviral factor in Zika and other flavivirus infections. Here, we accessed samples from 153 pregnant women (77 without and 76 with CZS) and 143 newborns (77 without and 66 with CZS) exposed to ZIKV conducted a case-control study to verify whether interferon alfa receptor 1 (IFNAR1) and interferon lambda 2 and 4 (IFNL2/4) single nucleotide polymorphisms (SNPs) contribute to CZS outcome, and characterized placenta gene expression profile at term. Newborns carrying CG/CC genotypes of rs2257167 in IFNAR1 presented higher risk of developing CZS (OR=3.41; IC=1.35-8.60; Pcorrected=0.032). No association between IFNL SNPs and CZS was observed. Placenta from CZS cases displayed lower levels of IFNL2 and ISG15 along with higher IFIT5. The rs2257167 CG/CC placentas also demonstrated high levels of IFIT5 and inflammation-related genes. We found CZS to be related with exacerbated type I IFN and insufficient type III IFN in placenta at term, forming an unbalanced response modulated by the IFNAR1 rs2257167 genotype. Despite of the low sample size se findings shed light on the host-pathogen interaction focusing on the genetically regulated type I / type III IFN axis that could lead to better management of Zika and other TORCH (Toxoplasma, Others, Rubella, Cytomegalovirus, Herpes) congenital infections.